Efektivitas Edukasi Puzzle Kesiapsiagaan Bencana Banjir Terhadap Tingkat Pengetahuan Siswa MI Fathul Ulum Sirau - Anisa Kholisoh, Nur; Dwi Aprilina, Happy (CV RIFAINSTITUT, 2023)
Flooding is a natural phenomenon that commonly occurs in areas with and happens all the time which result in causing loss of life and property. The village of Sirau is one such area in Banyumas Regency that frequently experiences flooding. Children are a vulnerable group during disasters. Their vulnerability is due to a limited understanding of disaster risks in their surroundings, resulting in a lack of preparedness to face disasters. Understanding disaster preparedness can reduce the negative effects of disasters. Also, recognizing the risk of disasters, raising awareness and reducing disaster risks is essential. Risk reduction can be achieved through flood disaster preparedness education in schools. This research aims to determine the effectiveness of flood disaster preparedness puzzle education on the knowledge level of students at MI (Islamic Elementary School) Fathul Ulum Sirau. The research employed a pre-experimental one-group pretest-posttest design approach. The sample for this research consisted of 32 respondents. The study was conducted at MI Fathul Ulum Sirau, Kemranjen District, Banyumas Regency. A purposive sampling technique was used for sample selection. Data collection was done using a knowledge questionnaire sheet. This research demonstrates an increase in knowledge after the education intervention. Before education, the mean score was 19.22, with a minimum score of 14 and a maximum score of 19. After the education, the mean score increased to 22.31, with a minimum score of 22 and a maximum score of 24. The Wilcoxon test result (p-value = 0.000) is significant. It can be concluded that puzzle games effectively convey disaster preparedness knowledge to students at MI Fathul Ulum Sirau.